2000
DOI: 10.1038/sj.leu.2401731
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics and prognosis of adult acute myeloid leukemia with internal tandem duplications in the Flt3 gene

Abstract: Internal tandem duplications of the Flt3 gene (Flt3/ITDs) are present in about 18% of all AML cases and are therefore one of the most frequent somatic gene mutations in AML. Little is known about the role of Flt3/ITDs in leukemogenesis or their clinical relevance. In this study we compared 18 samples with Flt3/ITDs and 63 AML samples without these mutations with respect to clinical prognosis, cytokine responsiveness, progenitor cell content and repopulation in the NOD/SCID mouse. We found that in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
179
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(196 citation statements)
references
References 36 publications
12
179
3
2
Order By: Relevance
“…Additionally, NOD/SCID mice were both insulitis-and diabetes-free throughout life . Subsequent transplant of NOD/SCID mice resulted in appreciably higher engraftment rates using fewer cells (Dick, 1996a;Bonnet and Dick, 1997), with ensuing xenografts preserving observed morphological, phenotypical, genotypical and biological characteristics of the donors AML cells (Dick, 1996b;Blair et al, 1998;Ailles et al, 1999;Rombouts et al, 2000a;Lumkul et al, 2002;Marx, 2003). Cells from patients with poor prognostic markers (e.g.…”
Section: Scid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, NOD/SCID mice were both insulitis-and diabetes-free throughout life . Subsequent transplant of NOD/SCID mice resulted in appreciably higher engraftment rates using fewer cells (Dick, 1996a;Bonnet and Dick, 1997), with ensuing xenografts preserving observed morphological, phenotypical, genotypical and biological characteristics of the donors AML cells (Dick, 1996b;Blair et al, 1998;Ailles et al, 1999;Rombouts et al, 2000a;Lumkul et al, 2002;Marx, 2003). Cells from patients with poor prognostic markers (e.g.…”
Section: Scid Modelsmentioning
confidence: 99%
“…Cells from patients with poor prognostic markers (e.g. high WBC, poor risk cytogenetics, FLT3-ITD positive, high CD34 expression) engrafted more efficiently in NOD/SCID mice than general AML cases (Ailles et al, 1999;Kondo et al, 1999;Rombouts et al, 2000a;Rombouts et al, 2000b;Lumkul et al, 2002;Pearce et al, 2006). However, there was a report showed that high WBC and FLT3-ITD were not predictors of engraftment success (Pearce et al, 2006).…”
Section: Scid Modelsmentioning
confidence: 99%
“…1 Recent screens have also identified a range of other point mutations in FLT3 in AML. [2][3][4] FLT3-ITD and FLT3-TKD mutants induce distinct disease states in mouse models 5 and although FLT3-ITD mutations are associated with a poor prognosis, [6][7][8][9] the prognostic implications of FLT3-TKD mutations are less clear. 9,10 The signaling events induced by the activated FLT3 mutants presumably converge to modulate gene expression changes contributing to survival, proliferation and maintenance of differentiation arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Although, FLT-3 is expressed in leukemias of both lymphoid and myeloid lineage (28), the development of small-molecule FLT-3 inhibitors was driven by the predominance of FLT-3 mutations in AML and their association with a poor prognosis for both adult (29) and pediatric patients (30,31). Results from experiments involving inhibitor, SU11657, in this study provided evidence of a relationship between FLT-3 activation and VEGF secretion.…”
Section: Discussionmentioning
confidence: 72%